Changes in sodium levels in Australian packaged foods between 2014 and 2019: an interrupted time series analysis of the impact of the Victorian Salt Reduction Partnership's media advocacy strategy - Emalie Rosewarne; Joseph Alvin Santos; Gian Luca Di Tanna; Maria Shahid; Carley Grimes; Kristy A. Bolton; Jacqui Webster; Bruce Neal; Mark Woodward; Daisy Coyle; Kathy Trieu (BMC, 2023)
Abstract Background The Victorian Salt Reduction Partnership (VSRP) implemented a media advocacy strategy (intervention) to stimulate food manufacturers to reduce sodium levels across targeted Australian packaged foods between 2017 and 2019. This study assessed changes in sodium levels of targeted and non-targeted packaged foods during the intervention (2017 to 2019) compared to before the intervention (2014 to 2016) in Australia. Methods Annually collected branded-food composition data from 2014 to 2019 were used. Interrupted time series analyses was conducted to compare the trend in sodium levels in packaged foods during the intervention (2017-2019) to the trend in the pre-intervention period (2014-2016). The difference between these trends was derived to estimate the effect of the intervention. Results A total of 90,807 products were included in the analysis, of which 14,743 were targeted by the intervention. The difference in before and during intervention trends between targeted and non-targeted food categories was 2.59 mg/100 g (95% CI: -13.88 to 19.06). There was a difference in the pre-intervention slope (2014, 2015, 2016) and intervention slope (2017, 2018, 2019) for four of 17 targeted food categories. There was a decrease in sodium levels (mg/100 g) in one food category: frozen ready meals (-13.47; 95% CI: -25.40 to -1.53), and an increase in three categories: flat bread (20.46; 95% CI: 9.11 to 31.81), plain dry biscuits (24.53; 95% CI: 5.87 to 43.19), and bacon (44.54; 95% CI: 6.36 to 82.72). For the other 13 targeted categories, the difference in slopes crossed the line of null effect. Conclusions The VSRP's media advocacy strategy did not result in a meaningful reduction in sodium levels of targeted packaged food products during the intervention years compared to trends in sodium levels before the intervention. Our study suggests media advocacy activities highlighting the differences in sodium levels in packaged food products and industry meetings alone are not sufficient to lower average sodium levels in packaged foods in the absence of government leadership and measurable sodium targets.